Virtual Reality Exposure Therapy in the Treatment of Driving Phobia - da Costa, Rafael Thomaz (2010)
A growing number of researches has appeared on virtual reality exposure therapy (VRET) to treat anxiety disorders. The purpose of this article was to review some evidences that support the VRET efficacy to treat driving phobia. The studies were identified through computerized search (PubMed/Medline, Web of Science, and Scielo databases) from 1984 to 2007. Some findings are promising. Anxiety/avoidance ratings declined from pre to post-treatment. VRET may be used as a first step in the treatment of driving phobia, as long as it may facilitate the in vivo exposure, thus reducing risks and high costs of such exposure. Notwithstanding, more randomized/controlled clinical trials are required to prove its efficacy.